2019
DOI: 10.1111/ajt.15378
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone exerts beneficial effects in patients with IPF undergoing single lung transplantation

Abstract: Pirfenidone demonstrated pleiotropic antiinflammatory effects in various experimental and clinical settings. The aim of this study was to assess the impact of previous treatment with pirfenidone on short-term outcomes after single lung transplantation (SLTx). Therefore, patients with idiopathic pulmonary fibrosis (IPF) who were undergoing SLTx were screened retrospectively for previous use of pirfenidone and compared to respective controls. Baseline parameters and short-term outcomes were recorded and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…This is partly due to the implementation of the Lung Allocation Score, prioritising patients most in need of transplantation and most likely to benefit. Dependent on age, comorbidities, local experience and donor availability, both single LTx and bilateral LTx are performed in patients with IPF [3,31].…”
Section: Antifibrotics In Ipfmentioning
confidence: 99%
See 3 more Smart Citations
“…This is partly due to the implementation of the Lung Allocation Score, prioritising patients most in need of transplantation and most likely to benefit. Dependent on age, comorbidities, local experience and donor availability, both single LTx and bilateral LTx are performed in patients with IPF [3,31].…”
Section: Antifibrotics In Ipfmentioning
confidence: 99%
“…Furthermore, VEIT et al [31] demonstrated a possible beneficial effect in IPF patients treated with pirfenidone undergoing single LTx, with shorter length of mechanical ventilation and intensive care stay, less severe primary graft dysfunction at 72 h, and lower incidence of acute cellular rejection within the first 30 days. ZHANG et al [48] also reported that IPF patients treated with pirfenidone had less histopathological evidence of acute lung injury (less diffuse alveolar damage and organising pneumonia) at time of LTx, and a trend towards less lymphocytic interstitial infiltration in lungs of patients treated with nintedanib.…”
Section: Effect On Peri-transplant Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…27 In the ASCEND trial Of Pirfenidone , A decline in FVC occured slowly in both chronic fibrotic lung disease and Idiopathic Pulmonary Fibrosis. 28,29 Acute exacerbation of IPF has the clinical, imaging, and histological characteristics of diffuse alveolar damage mimicking ARDS. 30 The applicability of these data to COVID-19 depends on the rapidity of action of antifibrotic drugs and their introduction before severe acute lung injury leading to diffuse alveolar damage( ARDS), threatens for Mechanical Ventilation has supervened…”
Section: Smokingmentioning
confidence: 99%